Coupled Solid‐State Diffusion of Li+ and O2 − During Fabrication of Ni‐Rich NMC Thin‐Film Cathodes Resulting in the Formation of Inactive Ni2O3 and NiO Phases - Sameer Rodrigues; Louis De Taeye; Philippe M. Vereecken (Advanced Materials Interfaces)
Abstract Ni‐rich Li(Ni1−x−yMnxCoy)O2 (NMC) is an attractive cathode material for Li‐ion batteries due to its high practical capacity (>200 mAh g−1). However, it is plagued by stability issues that, over multiple cycles or prolonged storage in air, degrade the material and decreases its electrochemical performance. A thin‐film model system can be used to simplify the cathode by omitting all passive components and electrode porosity and allow for an in‐depth analysis on the interfacial reactions that initiate the material degradation. In this work, the reactions occurring during the fabrication of thin film NMC are investigated. A lot of these reactions stemmed from the loss of active material from the film toward the substrate during annealing. Methods are then devised to reduce the unwanted reactions occurring during annealing. These included lowering the annealing temperature, compensating for material loss, as well as depositing a diffusion barrier between the substrate and NMC film. The findings in this paper outline the various conditions that affect the preparation of thin‐film NMC and give readers an overview of reactions to consider when developing thin‐film battery materials.